Tribal situation in India : issues and development - Joshī, Vidyuta; Upadhyaya, Chandrakant (Tribal Research and Training Institute, Gujarat Vidyapith, 2017)
Papers presented at the Regional Seminar on 'Issues and Development of Tribal Communities in Western India', 9-10 August 2015, organised at Tribal Research and Training Institute, Gujarat Vidyapith, Ahmedabad.